Acellular human glans extracellular matrix as a scaffold for tissue engineering: in vitro cell support and biocompatibility - Egydio,Fernanda M. (2015)
ABSTRACT Objectives: Diseases of the genitourinary tract can lead to significant damage. Current reconstructive techniques are limited by tissue availability and compatibility. This study aims to assess if the decellularized human glans can be used as a biomaterial for penile reconstruction. Materials and Methods: Samples of the glans matrices were descellularized. We evaluate the presence of collagen type I and III, and elastic fibers. Biocompatibility assays were performed to assess the cytotoxic and non-cytotoxic interactions between the acellular matrix and 3T3 cells. The matrices were seeded with mesenchymal stem cells and were assessed for viability and integration of these cells. Biomechanical tests in native tissue, descellularized matrix and seeded matrix were performed to characterize their biomechanical properties. Results: The tissue architecture of the decellularized matrix of human glans was preserved as well as the maintenance of the biomechanical and biological properties. The analyzes of glans seeded with mesenchymal stem cells revealed the integration of these cells to the matrices, and its viability during two weeks "in vitro". Conclusion: The decellularization process did not alter the biological and biomechanical characteristics of the human glans. When these matrices were seeded they were able to maintain the cells integrity and vitality.